Integrating Educational Technology to Address Disparities in Education: Implications for School Social Work. Issue 4 (1st September 2021) - Rogers, Kelli
Abstract: Educational disparity has been a long-standing social and political concern, and is a grand challenge for social work because of its implications for equal opportunity and social justice. As stewards of social justice in public K–12 educational settings, school social workers help students gain access to and effectively use resources and support necessary to maximize their potential in the educational process as well as identify areas of need that are not being addressed by the local education agency and community, and working to create services that address those needs. Several studies have applied educational technology interventions to address academic achievement equity issues and found improved performance on state test scores. Thus, 12 evaluation studies of educational technology in primary and secondary schools in the United States conducted after 2001 were synthesized, examining the impact of educational technology applications on student academic achievement. Although much of the research conducted emphasizes a positive correlation between these variables, not all approaches of using educational technology resulted in equally good performance, and not all students learning with educational technology learned better than those learning without educational technology under all conditions. This critique identifies both strengths and weaknesses of existing literature; suggests research priorities; and outlines specific implications for educators, policymakers, and school social workers.